Evaluation of Bioaerosoles in Health Center Environments in The City of Valencia, Venezuela - Noja Izzeddin; Luís Medina; Tomas Rojas (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2011)
Health center facilities are areas where patients who have a greater or lesser degree of immunological compromise congregate. In this context, the hospital environment is a space where nosocomial diseases could be acquired causing deterioration of the preexistent clinical condition. This study carried out evaluations in hospital environments at health centers in the city of Valencia, Venezuela, taking into account critical areas such as operating theatres. For sample collection, methodologies established by the Spanish Technical Standards were taken into account. The air samples taken over Nutritivo and Sabouraud cultivation media were incubated at 37°C for 24-72 hours, to determine the UFC/m3 for the air. Following a 24-hour incubation at 37°C, the bacterial charges (UFC/m3) were determined. Additionally, temperature and relative humidity were measured. Taxonomical identification was achieved through a computerized biochemical test (API galleries). Five out of the six health centers evidenced more than 10UFC/m3 and 20 UFC/m3 for the bacterial and fungal charges, respectively. These values are higher than those allowed by official legislation. The most frequently detected microorganisms were Staphylococcus spp, Pseudomonas aeruginosa, Bacillus spp., Acinetobacter lowfii, Aspergillus nidulans, A. terreus and Geotrichum candidum. The temperature and relative humidity were always higher than 20°C and 45%, whereas ranges established by the NTP 409 norm are 15-18ºC and 50-70%, respectively. It seems there is little commitment to applying correct measures to comply fully with standards for patient handling in critical areas, favoring an environment conducive to microbial development, as well as factors such as temperature, relative humidity and air conditioning systems, which do not comply with what is indicated in international technical standards.